1993
DOI: 10.1007/bf01637318
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss after cardiac transplantation: Effects of calcium, calcidiol and monofluorophosphate

Abstract: Of 203 patients who underwent cardiac transplantation and were given long-term treatment with cyclosporine and 0.3 mg/kg per day prednisone, 123 were studied prospectively for at least 6 months and 46 for up to 2 years to evaluate the effects on lumbar bone mineral density (BMD) and calcium metabolism of a combined therapy with calcium, calcidiol and disodium monofluorophosphate (MFP). The population was arbitrarily assigned to one of two groups. Group I consisted of patients who had a lumbar spine BMD Z score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 20 publications
1
27
1
2
Order By: Relevance
“…From mere "standard methods" (22), passing through "sera were measured using a specific F ion-sensitive electrode" (23) to "F concentration in serum were performed by laboratories located in four local universities laboratories using ion-specific potentiometry and were quality controlled" (24).…”
Section: Accuracy and Precision Of The Proposed Techniquementioning
confidence: 99%
“…From mere "standard methods" (22), passing through "sera were measured using a specific F ion-sensitive electrode" (23) to "F concentration in serum were performed by laboratories located in four local universities laboratories using ion-specific potentiometry and were quality controlled" (24).…”
Section: Accuracy and Precision Of The Proposed Techniquementioning
confidence: 99%
“…Following liver and heart trans plantation, treatment with fluoride resulted in increased bone mass and reduced fracture rates in a small series [33,63]. In view o f the low turnover bone remodelling that is present in patients with liver disease, a beneficial effect of osteoblast stimulation by fluoride seems reasonable, but may not apply to renal graft recipients with hyperparathy roid bone disease.…”
Section: Hyperparathyroidismmentioning
confidence: 99%
“…The use of corticosteroids is followed by spinal compression fracture in up to 35~ of patients [11. Moreover, some investigators have observed a 20% decrease in bone mineral density in patients with congestive heart failure awaiting transplantation [1,2~ but not others [3,41. In order to permit further understanding of the mechanism involved in such demineralisation, We studied bone mineral density and plasma calciotropic hormone levels in 30 male patients awaiting heart transplantation.…”
Section: Introductionmentioning
confidence: 99%